Legalisasi Ganja di Uruguay dan Kanada: Dampak terhadap Kesejahteraan Masyarakat Nasional - Nada Gavrila Wasisto; Sesilia Rainaputri Jans (Jurnal Sentris, 2022)
ABSTRACT The legalization of cannabis has been a trend to be done by countries because it is seen as beneficial in many ways. Marijuana is seen as a drug which has less negative impacts, or can be said “manageable” hence receiving much support from the society to be legalized in a country. Cannabis legalization, either medical or non medical marijuana, is believed to positively impact the welfare of society. Uruguay and Canada are the first and second countries which legalized non medical marijuana through the establishment of a specific marijuana policy to regulate various activities related to marijuana. However, the established marijuana legalization policy has not necessarily proven to give advantages to society. In addition, the impacts of the legalization itself can not only be seen from the fact that the countries have legalized marijuana, rather how the legalization is regulated in the policy. Thus, this research will analyze how marijuana is legalized in the national policy of Uruguay and Canada, and compare the impacts of the policy towards human welfare through the perspective of Social Welfare Theory by Elizabeth Wickenden.